Atlantic Nessologies: Image, Territory, Value - Francisco-]. Hernández Adrián (Studies in 20th & 21st Century Literature, 2006)
This essay addresses the emerging field of Atlantic Studies and questions the status of "the Atlantic" as an object of study. Rather than assuming a self-evident grid where Atlantic cultural phenomena oscillate between such poles as "centers and peripheries," or "the colonizer and the colonized," I consider a different formulation of the Atlantic. Taking as a starting point an analysis of a poem by Tomás Morales, a modernista poet from the Canary Islands, my essay outlines the notion of "Atlantic nessologies." Three parallel departures are offered from this analysis: image (or the realm of the imaginary); territory (or spatial and geopolitical inscriptions of the Atlantic in western space-time); and value (or those ethical and political dimensions that can be drawn from Atlantic specificities). Critical engagements with the Atlantic, my essay concludes, can be anchored in "nessological" readings in which neither local, singular perspectives contained in islands, nor wider, more panoramic views of the Atlantic, ought to escape critics. Instead, the work of engaging the Atlantic from multiple perspectives and locations should express itself as a field of critical/political strategies coordinated against perennial re-inscriptions of Eurocentric totality.
Keywords: Atlantic Studies; colonialism; Tomás Morales; modernista; Canary Islands; nessology; image; imaginary; territory; space; geopolitical; space-time; nessological